Two-dimensional Gel Analysis of Total Seed Protein of Horse Gram (Macrotyloma uniflorum) for Identification of their Proteomic Diversity - Sharma, Netrapal; Bisht, Satpal Singh; Gupta, Sanjay; Dewali, Seeta; Parveen, Nagma; Pant, Rohit (Asian Journal of Biological and Life Sciences)
Horse gram (Macrotyloma uniflorum) is a popular pulse in the Kumaun region of Uttarakhand, locally known as Gahat dal and Kulti. An experiment was conducted with 5 horse gram cultivars having different grain colors. Total seed protein was isolated and quantified with standard protocols. Five protein samples were subjected to one-dimensional (1D) and two-dimensional (2D) gel for proteomic analysis. 300g of each sample was loaded onto immobilized pH gradient (IPG) strips (3–10 pH Linear, 18 cm) and kept for Iso-Electric Focusing (IEF) and SDS-PAGE. The gels were scanned using a scanner and analyzed for proteomic diversity. Basically, two major clusters were constructed, and samples 1, 2, and 3 are in group one and 4 and 5 are in group two, and group one has two further sub-clusters. Sample one was separately clustered based on the number of spots presented on the 2D gel and based on its color. The analysis of variance revealed that the genotypes observed had highly significant differences. Further study is needed for the identification of unique peptides presented by protein sequencing. The proteomic analysis of total seed proteins could be useful for the development of nutraceuticals and food-to-food fortification. This study’s current proteome and other proteomic information will be extremely useful to horse gram breeding programmes.
Keywords: 2D gel; Horse gram; Kumaun; Protein; SDS-PAGE